Changes in Sleep Patterns in Korean Early Adolescents during Sexual Maturation - Taehwan Han; Kyu Young Chae; Eun-Gyong Yoo; Mo Kyung Jung; Eun Kyo Ha; Man Yong Han; Hye Mi Jee; Seonkyeong Rhie (Korean Child Neurology Society, 2022)
Purpose Teenagers' sleep patterns show physiological delays influenced by sexual maturation and other external time-related factors. However, Korean adolescents show differences in the onset of pubertal development and have shorter sleep durations than other adolescents worldwide. Therefore, we assessed sleep patterns and sexual maturation in Korean early adolescents to evaluate changes in sleep patterns in relation to sexual maturation in early adolescents with sleep deprivation. Methods From March to August 2017, we surveyed children aged 10 to 12 years in Seongnam (Seongnam Atopy Project). We evaluated items related to sleep and sexual maturation, assessed sleep duration and sleepiness scale scores, and analyzed the relationships of sleep parameters with sex, height, weight, and sexual maturation rating (SMR). Results In total, 620 children were included. Sleep duration was 8.63±0.81 hours in boys and 8.40±0.98 hours in girls. Sleep started from PM 11:00±AM 0:47 in boys and PM 11:13±AM 1:06 in girls, and ended at AM 7:38±AM 0:27 in boys and AM 7:34±AM 0:27 in girls. After adjusting for sex and standardized body mass index, bedtime was delayed as the SMR increased (mean delay for each rating increase, 0.251 hours; P=0.001; 95% confidence interval [CI], 0.105 to 0.397). SMR did not influence the wake-up time, although sleep duration decreased as the SMR increased (mean decrease for each rating increase, 0.258 hours; P=0.001; 95% CI, -0.403 to -0.114). The sleepiness scale scores showed no relationship with SMR. Conclusion Sleep patterns, especially sleep duration and bedtimes, show changes with sexual maturation in adolescents, who are vulnerable to sleep deprivation.